Service Supply Chain Risk Management: Distinctions from Manufacturing - Thi Huong Tran; Sebastian Kummer (Innovations and Strategies for Logistics and Supply Chains: Technologies, Business Models and Risk Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 20, 2015)
In recent decades, service sector has become a main driver of most economies. This sector has unique characteristics entailing many distinctions in operations management and supply chain management compared with manufacturing. However, from academic and practical standpoints, the focus in supply chain management has been strongly leaned toward the goods-dominant logic. So far, the conceptual as well as empirical research on service supply chain risk management (SSCRM) has been scarce. This paper, therefore, attempts to investigate SSCRM with focus on its distinctions from manufacturing through two steps. At the first step, authors review prior research to explore the distinctive features of service supply chain and identify typical supply chain risk management (SCRM) strategies which are effectively applied to manufacturing industry. As a second step, we conduct a case study research of four service providers in telecom and logistics industry in Austria in order to investigate influences of these different features on SSCRM. Findings present distinctive risks arising in service supply chain, features of SSCRM, and efficiency extent of implementing manufacturing SCRM strategies to SSCRM.
10419/209189; https://econpapers.repec.org/RePEc:zbw:hiclpr:20
Keywords: 650; Risk Management; Service Supply Chain; Manufacturing Supply Chain; Distinctive Attributes